2020
DOI: 10.1016/j.molcel.2019.10.030
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Noncoding Locus Regulates Random Monoallelic Xist Expression across a Topological Boundary

Abstract: Highlights d The Tsix-TAD regulates not only Tsix but also Xist, in part via LinxP d LinxP influences choice making during random XCI by regulating Xist expression in cis d Linx transcription affects local topology but is not necessary for Xist regulation d LinxP is conserved in sequence and synteny across placental mammals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 113 publications
8
73
1
Order By: Relevance
“…Next, we investigated the regulatory landscape of the Xic from a structural perspective. The Xic is divided into two functionally opposing domains (van Bemmel et al, 2019;Galupa et al, 2020;Nora et al, 2012;Spencer et al, 2011;Tsai et al, 2008): TAD-D, which contains the noncoding genes Tsix, Xite and Linx, which are repressors of Xist; and TAD-E, which harbors Xist itself and its activators, the non-coding Jpx and Ftx and the protein-coding Rlim/Rnf12 ( Figure 5C). First, we noticed a gradual strengthening of the TAD border between TAD-D and TAD-E during reprogramming, as indicated by a drop in the insulation score ( Figure 5C).…”
Section: Remodeling Of the X-inactivation Center Leads To Xist Downrementioning
confidence: 99%
“…Next, we investigated the regulatory landscape of the Xic from a structural perspective. The Xic is divided into two functionally opposing domains (van Bemmel et al, 2019;Galupa et al, 2020;Nora et al, 2012;Spencer et al, 2011;Tsai et al, 2008): TAD-D, which contains the noncoding genes Tsix, Xite and Linx, which are repressors of Xist; and TAD-E, which harbors Xist itself and its activators, the non-coding Jpx and Ftx and the protein-coding Rlim/Rnf12 ( Figure 5C). First, we noticed a gradual strengthening of the TAD border between TAD-D and TAD-E during reprogramming, as indicated by a drop in the insulation score ( Figure 5C).…”
Section: Remodeling Of the X-inactivation Center Leads To Xist Downrementioning
confidence: 99%
“…The mechanism by which hundreds of genes are repressed in a coordinated manner has captured the interest of researchers for over half a century but is by no means the only aspect of the mammalian dosage compensation system that remains a puzzling wonder of biology 1 . The choice of the X chromosome to switch off, either maternal or paternal, is widely accepted to be random in placental mammals, and recent evidence in mice suggests a stochastic process for which a few components have been identified 2,3 . A mechanism for generating randomness is difficult to establish on a molecular basis but ultimately may inspire technology as well as cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified another potential and evolutionarily conserved modulator of Xist, called Linx. The report highlights the contextual role played by Linx as a silencer of Xist when in its original location in Tsix TAD and as an enhancer when artificially placed in Xist TAD (Galupa et al, 2020) The conserved cRE identified in mouse is actually designated as the P2 promoter that has been demonstrated to bind YY1 and CTCF (Johnston et al, 1998;Makhlouf et al, 2014;Navarro et al, 2006;Sun et al, 2013). As opposed to our observation of female-specific enrichment of CTCF in mouse (Xi) (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, when it is placed in Xist TAD, it serves as an enhancer of Xist (Galupa et al, 2020). Besides the X-chromosomal cis-acting modulators, the autosomally encoded trans-acting factors such as the core pluripotency factors -Oct4, Sox2, Nanog, Klf4 and c-Myc link the two developmental events of differentiation and XCI (Schulz et al, 2014), by regulating Xist (Navarro et al, 2008;Nesterova et al, 2011), Tsix (Donohoe et al, 2009;Navarro et al, 2010) and Rnf12 (Navarro et al, 2011), Linx (Galupa et al, 2020). Thus, it can be convincingly stated that Xist expression is robustly regulated by a multitude of cis and trans factors acting either synergistically or independently to ensure accurate execution of the developmentally important process of XCI.…”
Section: Introductionmentioning
confidence: 99%